Evaluating the risk of eavesdropping a visible light communication channel. Issue 6 (1st December 2018) - Marin‐Garcia, Ignacio; Guerra, Victor; Chavez‐Burbano, Patricia; Rabadan, Jose; Perez‐Jimenez, Rafael
Abstract : Visible light communication (VLC) technologies are becoming a method to communicate with a wide range of devices. One of VLC's biggest proposed advantages is the inherent security that this technology provides. The concept of securing on VLC is based on its indoor use since optical radiation is confined by walls. However, doors and windows are usually present in any inhabited structure through which the optical signal can leak and be detected by external devices. In this study, the signal leaked through such a window and the risk of eavesdropping the VLC‐based channel may have is studied. In this way, a risk evaluation parameter, which includes different variables, is proposed and analysed.